Current Status and Challenges of Ultrasound-Guided Ablation Therapy for Liver Cancer - Yan ZHOU; Jianmin DING; Yandong WANG; Xiang JING (Zhongliu Fangzhi Yanjiu)
Ultrasound-guided local ablation therapy for liver tumors has extensive clinical application because of its minimal invasiveness, proven effectiveness, low complication rates, and suitability for repeat treatments. Ultrasound-guided interventional therapy has continuously evolved in terms of the following: technological advancements, from the initial utilization of percutaneous ethanol injection to thermal ablation therapies exemplified by radiofrequency ablation and microwave ablation and presently advancing toward emerging techniques such as irreversible electroporation; imaging methods, from conventional ultrasound guidance to contrast-enhanced ultrasound and fusion imaging for precise guidance and assessment; supplementary strategies, from monotherapy to auxiliary method and synergistic therapy; and innovative treatment concepts, from early-stage small hepatocellular carcinoma to intermediate and even large liver cancers. The development of ultrasound-guided local ablation of liver cancers has progressed from an initial phase of rapid advancement to a mature stage characterized by further enhancements. This article provides a comprehensive overview of the status of technical equipment, treatment processes, efficacy, complications, and challenges encountered in ultrasound-guided local ablation for liver tumors, with the objective of offering valuable insights for interventional ultrasound physicians.